2019
DOI: 10.3390/cells8080805
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Plasticity of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is one of the most common and life-threatening leukemias. A highly diverse and flexible metabolism contributes to the aggressiveness of the disease that is still difficult to treat. By using different sources of nutrients for energy and biomass supply, AML cells gain metabolic plasticity and rapidly outcompete normal hematopoietic cells. This review aims to decipher the diverse metabolic strategies and the underlying oncogenic and environmental changes that sustain continuous growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 126 publications
(176 reference statements)
3
121
0
Order By: Relevance
“…Recent studies suggest that AML cells have considerably metabolic plasticity [9] and our present study shows that AML cells derived from different patients are also characterized by metabolic heterogeneity, that is the antiproliferative and proapoptotic effects of various metabolic inhibitors varied between patients. This was seen after treatment with inhibitors of glycolysis but also after targeting of mitochondrial metabolism through inhibition of glutaminolysis and fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Recent studies suggest that AML cells have considerably metabolic plasticity [9] and our present study shows that AML cells derived from different patients are also characterized by metabolic heterogeneity, that is the antiproliferative and proapoptotic effects of various metabolic inhibitors varied between patients. This was seen after treatment with inhibitors of glycolysis but also after targeting of mitochondrial metabolism through inhibition of glutaminolysis and fatty acid oxidation.…”
Section: Discussionsupporting
confidence: 51%
“…Complex metabolic capacities may contribute to the aggressiveness of AML, allowing cells to survive under higher metabolic demands. However, AML patients are heterogeneous with regard to metabolic regulation [8][9][10][11][12] and in this study we attempt to further investigate if patients are heterogeneous also with regard to the antileukemic effects of metabolic targeting.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The current progresses in AML mainly include improvements on treating opportunistic infectious diseases, advances on supportive care, and reduce of complications after allogeneic BM transplantation; however, the therapeutic effects are unsatisfactory, with a 5-year survival rate of 40% for younger patients (18-60 years) and a 5-year survival rate of 10% for the elder patients (age above 60 years), and AML is still a life-threatening disease. 1,3,4 Thus, rational development of novel strategies to improve the treatment outcomes of AML is important. Since emerging studies have revealed that the association of molecular aberrations with the prognosis may contribute to guide therapeutic decisions, exploring novel biomarkers that being identified for AML prognosis is desperately needed.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of drugs used to treat cancers target actively proliferating cells (e.g., taxanes like paclitaxel or docetaxel, or cyclin-dependent kinase inhibitors like abemaciclib or palbociclib), making them less effective against LSCs. Importantly, LSCs, like other leukemia cells appear to be more dependent upon mitochondria for energy production than most cancer cells (60)(61)(62), and thus may be more sensitive to the drug cocktails identified here. This hypothesis is currently under active investigation.…”
Section: Discussionmentioning
confidence: 87%